Pure hepatocellular carcinoma originates from an ectopic liver nodule located in the pancreas - Braun, Marcin; Kuncman, Wojciech; Teresiński, Leszek; Kupnicki, Piotr; Jesionek-Kupnicka, Dorota; Kordek, Radzislaw (Contemporary Oncology/Współczesna Onkologia, 2017)
Ectopic liver (EL) is a rare congenital abnormality, which is localised most commonly in the wall of the gallbladder. Histoarchitectural abnormalities, which lead to impaired transfer of blood and bile, as well as well demarcation, are characteristic features of ectopic liver nodules. Both features may explain the discrepancies between hepatocellular carcinoma (HCC) cases originating from ectopic liver in comparison to HCC cases originating from orthotopic liver: the strong propensity of ectopic liver to the development of HCC. The latter feature may be linked to the better treatment prognosis in patients with HCC originating from ectopic liver tissue in comparison to those with HCC within orthotopic liver. In this paper, we discuss these differences based on a unique case of pure HCC, which developed in a small ectopic liver nodule in the pancreas.